Nonlinear one-dimensional guided wedge waves - Lomonosov, Alexey M.; Pupyrev, Pavel D.; Hess, Peter; Mayer, Andreas P. (Physical review. B, Condensed matter and materials physics, 2015)
The experimental observation of an efficient second-order nonlinearity with dominating frequency upconversion is reported for one-dimensional (1D) guided elastic waves localized at solid edges. These 1D acoustic wedge waves are a fundamental type of elastic wave with a phase velocity below that of surface and bulk waves and no coupling to them. Acoustic pulses, showing steepening, narrowing, and spiking to shocklike profiles, were generated and detected by a laser-based pump-probe setup. Shock formation is described by a nonlinear evolution equation, which allows the characteristic features of 1D guided shock waves to be predicted that differ from their bulk and surface analogs.